Co-occurrence patterns between false coral snake Atractus latifrons (Günther, 1868) (Serpentes: Dipsadidae) and venomous coral snakes from the Amazon - ALMEIDA,PAULA CAROLINA R. DE (2022)
Abstract Batesian mimicry may result in remarkable cases of phenotypic convergence that represent classic examples of evolution through natural selection. The existence of mimicry systems among coral snakes, however, remains controversial because of contradictions between the predictions of mimetic theory and the empirical patterns of co-occurrence and species abundance. Here, we analyze the geographic distribution of coral snake species of the genus Micrurus and populations of the false coral snake Atractus latifrons in Amazonia, and perform ecological niche modeling (ENM) analyzes to generate potential geographic distributions of species of Micrurus and A. latifrons, identify patterns of co-occurrence and assess whether the distribution of A. latifrons coincides with the distribution of Micrurus species, which could suggest the existence of a possible mimetic relationship between the species. We identified six Micrurus species that may represent mimetic models for A. latifrons. The results of the co-occurrence analysis corroborates the results from ENM, indicating that chromatic patterns of A. latifrons and their respective model species are aggregated. Our study suggests that all color patterns of A. latifrons – including the tricolor monads, and the more common tricolor dyads and tricolor tetrads – may benefit from the resemblance with other Micrurus species as perfect and imperfect mimics.